Strategi Penerapan Disiplin Positif Untuk Meningkatkan Perilaku Siswa di MTS Ciwedus - Hana Nurzakiah; Fitri Amelia; Khamdiallah Khamdiallah (Lembaga Pengembangan Kinerja Dosen, 2024)
The implementation of positive discipline in schools plays a crucial role in shaping students' character and behavior. At MTs Ciwedus, disciplinary issues often arise due to the ineffectiveness of the methods used by educators. This study aims to identify and analyze the effectiveness of implementing positive discipline on students' behavior at MTs Ciwedus. This research employs a qualitative method with a case study approach. Data were collected through observations, in-depth interviews, and documentation. The subjects of the study were students and educators at MTs Ciwedus. The results show that the implementation of positive discipline can reduce negative student behaviors and enhance a conducive learning environment. Educators who apply positive discipline tend to be more successful in building good relationships with students, thus creating a more effective learning environment. The implementation of positive discipline at MTs Ciwedus has proven to be effective in addressing disciplinary issues and improving students' positive behavior. It is recommended that the school continues to implement and develop this method to achieve more optimal results.